Cognitive Outcomes for Essential Tremor Patients Selected for Thalamic Deep Brain Stimulation Surgery Through Interdisciplinary Evaluations - Jones, Jacob D.; Orozco, Tatiana; Bowers, Dawn; Hu, Wei; Jabarkheel, Zakia; Chiu, Shannon; Ramirez-Zamora, Adolfo; Foote, Kelly; Okun, Michael S.; Wagle Shukla, Aparna (Frontiers in Human Neuroscience, 2020)
Objective: Deep brain stimulation (DBS) targeted to the ventral intermediate nucleus of the thalamus is effective for motor symptoms in essential tremor (ET), but there is limited data on cognitive outcomes. We examined cognitive outcomes in a large cohort of ET DBS patients (pre-DBS and 1+ year after DBS). Methods: In a retrospective analysis, we used a repeated-measures ANOVA testing to examine whether the age of tremor onset, age at DBS surgery, hemisphere side implanted with lead, unilateral versus bilateral implantations, and presence of surgical complications influenced the cognitive outcomes. Neuropsychological outcomes of interest were verbal memory, executive functioning, working memory, language functioning, visuospatial functioning, and general cognitive function. Results: We identified 50 ET DBS patients; 29 (58%) males; mean age of tremor onset was 35.84 (± 21.50) years with median age 38 years. The mean age at DBS was 68.18 (± 10.07) years. There were 37 unilateral 30 left, 7 right and 13 bilateral brain implantations. In the subgroup analysis, there was a significant interaction between assessment (pre vs. post) and age of tremor onset (< 38 vs. > 38 years); F1,30 = 4.47; p =.043 for working memory. The posthoc testing found improvements for younger onset ET. Similarly, there was a significant interaction between assessment (pre vs. post) and complications vs. no complications subgroups; F1,45 = 4.34; p =.043 for verbal memory with worsening scores seen for ET patients with complications. The remaining tests were not significant. Conclusion: In this large cohort of ET, DBS was not accompanied by a significant decline for many cognitive domains. These outcomes were possibly related to the selection of patients with normal cognitive functioning before surgery, unilateral DBS implantations for the majority, and selection of patients with optimal response to DBS.